Unmasking inborn errors of immunity: identifying the red flags of immune dysregulation - Cortesi, Manuela; Dotta, Laura; Cattalini, Marco; Lougaris, Vassilios; Soresina, Annarosa; Badolato, Raffaele (Frontiers in Immunology, 2024)
Inborn errors of immunity (IEI) are rare diseases that affect the immune system. According to the latest International Union of Immunological Societies (IUIS) classification, 485 different IEI have been identified. Even if increased susceptibility to infections is the best-known symptom, IEI are no longer defined by the higher likelihood of infections alone. Immune dysregulation with autoimmune disease and hyperinflammation, lymphoproliferation, and malignancy are common manifestations and could be the only symptoms of IEI that must be recognized. An exclusive focus on infection-centered warning signs would miss around 25% of patients with IEI who initially present with other manifestations. Timely and appropriate diagnosis and treatment are essential to enhance the quality of life (QoL) and, in some cases, survival, as patients are susceptible to life-threatening infections or autoimmunity. In addition, the advantage of early diagnosis in IEI with immune dysregulation (i.e. CTLA4 deficiency, LRBA deficiency, NF-kB1/NF-kB2 deficiency, activated phosphoinositide 3-kinase delta syndrome -APDS-) is the initiation of targeted therapies with precise re-balancing of the dysregulated immune pathways (i.e., biologicals, selective inhibitors) or definitive therapy (i.e., HSCT).